The impact of water conservation policies on the reallocation of agricultural water-land resources - Kavand, Hadis; Ziaee, Saman; Mardani Najafabadi, Mostafa (Frontiers in Water, 2023)
The effects of policies on farmers' profit have a key role in their adoption by the farmers and their operationalization at the basin level. The present research explored the effects of water resources conservation policies on optimal cropping pattern and farmers' profit in the Zayanderud basin located Iran using a combined hydrological-economic model composed of WEAP and multi-objective (MOP) models for the assessment of the effects of the A2 climate change scenario with or without the conservation policies. The results showed that climate change will reduce crop yields by 0.5–4%, will decrease water availability by 12–19%, and will increase crop water requirements by 0–4%. It was also found that the adoption of the policy of changing irrigation technology along with the policy of limiting groundwater use will alleviate the effects of climate change on the farmers' profit, will enhance their planned return per unit area by 5%, and will increase the economic efficiency of water use from 5,283 to 6,002 IRR/m3. But, the policy of increasing water price cannot improve the farmers' profit at the basin level and the economic efficiency of water use although it can reduce water use. So, proving the improvement of profit and livelihood of the farmers by applying combined water resources conservation policies can play a significant role in motivating farmers to accept these policies, operationalizing optimal water resources management, and resolving conflicts over water use in this basin.